Patterns of advice, trust and communication among the employees of the UP Main Library using Social Network Analysis (SNA) - Bamba, Frederick L. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
This study aimed to uncover the informal advice, trust and communication networks present among the employees of the UP Main Library. The study used a questionnaire distributed to the entire UP Main library staff population of 57 employees. The questionnaire asked each respondent to identify a co- worker they seek work related/technical advice from, a co-worker they trust to support their career growth and development, and a co-worker they regularly talk to. The results were then subjected to visualization and analysis.